Pengembangan Sistem Monitoring Aktivitas Jaringan pada Mikrokomputer Raspberry Pi - Frondy Fernanda Ferdianto; Widhi Yahya; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The Internet of Things(IoT) development have been improved very well, the integration of device in various field become the prove. The IoT device number of use also increase, from this fact, IoT devices management become the challenge to solve. The solution of this challenge is network monitoring system that run effectively. The system must handle the constraint of IoT device power and computational performance too. The implementation of monitoring using SNMP is not effective, because the size of paket for transmission is big and not all component of SNMP protocol being used. The monitoring system that being developed use UDP protocol because of its simplicity and light-weight to IoT devices. The selection of data structure and database also give contribution to effectiveness of this system. The IoT devices that used for the development is Raspberry Pi, this device has been selected because of the good integration with the other sensors, so it will make the development of this system in future become possible. This system monitors the device resource and network activity, then the result will be displayed on a graph, so the user can get the information of the result. The network monitoring system that being developed is effective, because the use of device's resource is small. In one transaction, the data paket size which transmitted is 309 bytes, this is smaller than SNMP-based monitoring system.